2023
DOI: 10.46690/ager.2023.10.05
|View full text |Cite
|
Sign up to set email alerts
|

Pore-GNN: A graph neural network-based framework for predicting flow properties of porous media from micro-CT images

Mohammed K. Alzahrani,
Artur Shapoval,
Zhixi Chen
et al.

Abstract: This paper presents a hybrid deep learning framework that combines graph neural networks with convolutional neural networks to predict porous media properties. This approach capitalizes on the capabilities of pre-trained convolutional neural networks to extract ndimensional feature vectors from processed three dimensional micro computed tomography porous media images obtained from seven different sandstone rock samples. Subsequently, two strategies for embedding the computed feature vectors into graphs were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…This approach makes it possible to learn complex graph relationships in spatially irregular data. Despite monitoring networks/systems providing limited observations, GNN-based methods are highly effective at capturing dependencies in graphs (Fan et al, 2019;Li et al, 2021;Wu et al, 2021Wu et al, , 2022, and have demonstrated efficacy in groundwater modeling (Alzahrani et al, 2023;Bai & Tahmasebi, 2023;Feng et al, 2023). GNNs can be adapted for modeling solute transport in the subsurface by using nodes and edges that are analogous to contamination monitoring and solute migration.…”
Section: Introductionmentioning
confidence: 99%
“…This approach makes it possible to learn complex graph relationships in spatially irregular data. Despite monitoring networks/systems providing limited observations, GNN-based methods are highly effective at capturing dependencies in graphs (Fan et al, 2019;Li et al, 2021;Wu et al, 2021Wu et al, , 2022, and have demonstrated efficacy in groundwater modeling (Alzahrani et al, 2023;Bai & Tahmasebi, 2023;Feng et al, 2023). GNNs can be adapted for modeling solute transport in the subsurface by using nodes and edges that are analogous to contamination monitoring and solute migration.…”
Section: Introductionmentioning
confidence: 99%